Penyuluhan Strategi Pemasaran STP untuk Meningkatkan Daya Saing Forum Komunikasi UMKM di Donokerto, Turi, Sleman, Yogyakarta - Sari, Niken Permata; Khairi, Ardhi; Sari, Utami Tunjung (Society : Jurnal Pengabdian Masyarakat, 2023)
The large number of MSME actors selling similar products can increase competition in the market. Therefore, to survive high competition, MSME business actors need to understand marketing strategies, especially segmentation, targeting, and positioning (STP). Partners in this community service program are members of the "Forum Komunikasi UMKM in the Donokerto Village." This type of business is engaged in the field of crafts and also culinary. The obstacle from partners is that the income earned is not maximized even though they have made sales through an online business. Therefore, counseling is held in the form of delivering material about STP to increase members' understanding and can be practiced for business operations in the future. The result of this program is that all activities run smoothly, participants are actively involved, and participants' understanding of STP has increased.